THE DEVELOPMENT OF SOCIAL WELFARE THROUGH ISLAMIC SOCIAL SECURITY SYSTEM - Manurung, Saprinal; Amsari, Syahrul; Nasution, M Yasir; Sugianto, Sugianto (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this article is to analyze the relationship between developments of social welfare through the Islamic social security system to create balance in human life. Based on a literature study using qualitative analysis, we try to describe how the instruments of the Islamic social security system can be contributed to the development of the social and economic welfare of Muslims. Islam emphasizes two key factors in the balance of development, namely the development of natural resources and human resources. These two factors will be able to balance between the physical and spiritual, worldly life and hereafter, material and spiritual, which presents present a certainty in the form of goodness (al-shalâh) and happiness (assa'adah). In implementing the principle of balanced development, Islam offers a social security system that creates service to fellow-beings, obligations to society, self-help and collective action for the common good by emphasizing the principles of dignity of person, equality of man and the welfare of humanity. So that the existence of individuals, society and governments have a legal and moral obligation to take care and fulfil the needs of the poor and needy sections of the society irrespective of their faith and relationship with donor